Drug access, patents and global health : 'chaffed and waxed sufficient - Heywood, Mark (2002)
Focuses on the need to understand why and how the notion of health has undergone substantial changes and widened its scope. Looks at the forces that are contributing to this redefinition, and the implications for governments, multinational pharmaceutical companies and ordinary people.